2014
DOI: 10.1371/journal.pone.0098356
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Gq/11 Genes Does Not Abolish Melanopsin Phototransduction

Abstract: In mammals, a subset of retinal ganglion cells (RGCs) expresses the photopigment melanopsin, which renders them intrinsically photosensitive (ipRGCs). These ipRGCs mediate various non-image-forming visual functions such as circadian photoentrainment and the pupillary light reflex (PLR). Melanopsin phototransduction begins with activation of a heterotrimeric G protein of unknown identity. Several studies of melanopsin phototransduction have implicated a G-protein of the Gq/11 family, which consists of Gna11, Gn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…Previous studies have found the absorption maxima of purified melanopsins and the maximal spectral sensitivity of melanopsin-expressing cultured cells are both around 480 nm (13, 14, 16 -21). Although some G q -independent signaling by melanopsin has been suggested (22), a variety of melanopsins are reported to show light-dependent G q activation in vivo and in vitro (14,17,18,(23)(24)(25)(26), consistent with their high sequence similarity with the invertebrate visual pigments, which also use G q -dependent signaling (7,9) (Fig. 1A).…”
mentioning
confidence: 61%
“…Previous studies have found the absorption maxima of purified melanopsins and the maximal spectral sensitivity of melanopsin-expressing cultured cells are both around 480 nm (13, 14, 16 -21). Although some G q -independent signaling by melanopsin has been suggested (22), a variety of melanopsins are reported to show light-dependent G q activation in vivo and in vitro (14,17,18,(23)(24)(25)(26), consistent with their high sequence similarity with the invertebrate visual pigments, which also use G q -dependent signaling (7,9) (Fig. 1A).…”
mentioning
confidence: 61%
“…In 3 ipRGCs (9%), no detectable level of any of Gq/11 mRNA was found. These data implicate the role of Gna11 and Gna14 in ipRGCs . The involvement of G proteins in melanopsin signaling was also analyzed in knockout mice lacking the respective G proteins.…”
Section: Melanopsin‐regulated Signaling Pathwaymentioning
confidence: 64%
“…Therefore, Chew et al . suggested the compensatory upregulation from the remaining Gq/11. The presence of other Gq/11‐independent pathway in vivo in ipRGCs was also suggested, which is conceivable since other G proteins, such as Gi/o, were also shown to be activated by the photoexcited melanopsin .…”
Section: Melanopsin‐regulated Signaling Pathwaymentioning
confidence: 98%
See 2 more Smart Citations